Investigating Eye Contact Effect on People’s Name Retrieval in Normal Aging and in Alzheimer’s Disease - Lopis, Desirée; Conty, Laurence (Frontiers in Psychology, 2019)
Difficulty in recalling people’s name is one of the most universally experienced changes in old age and would also constitute one of the earliest symptom of Alzheimer’s Disease (AD). Direct gaze, i.e. another individual’s gaze directed to the observer that leads to eye contact, has been shown to improve memory for faces and concomitant verbal information. Here we investigated whether this effect extends to memory for Face-Name association and can thus enhance names’ retrieval in normal ageing and in AD, at the early stage of the disease. Twenty AD patients, 20 older adults and 25 young adults participated in our study. Subjects were presented with faces displaying either direct or averted gaze in association with a name presented orally. They were then asked to perform a surprise recognition test for each pair of stimuli, in a sequential fashion (i.e. first categorizing a face as old or new and then associating a name using a forced-choice procedure). Results showed that direct gaze does not improve memory for Face-Name association. Yet, we observed an overall direct gaze memory effect over faces and names independently, across our populations, showing that eye contact enhances the encoding of concomitantly presented stimuli. Our results are the first empirical evidence that eye contact benefits memory throughout the course of ageing and lead to better delimit the actual power of eye contact on memory.